2021
DOI: 10.1007/s00705-021-05149-0
|View full text |Cite
|
Sign up to set email alerts
|

ddPCR increases detection of SARS-CoV-2 RNA in patients with low viral loads

Abstract: RT-qPCR detection of SARS-CoV-2 RNA still represents the method of reference to diagnose and monitor COVID-19. From the onset of the pandemic, however, doubts have been expressed concerning the sensitivity of this molecular diagnosis method. Droplet digital PCR (ddPCR) is a third-generation PCR technique that is particularly adapted to detecting low-abundance targets. We developed two-color ddPCR assays for the detection of four different regions of SARS-CoV-2 RNA, including non-structural (IP4-RdRP, helicase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…15 This observation could also be a result of a reporting bias in cases where the initial diagnosis of viral pneumonia in association with a suspected COVID-19 infection was established, but not revised promptly after ruling out SARS-CoV-2 by means of polymerase chain reaction testing. 16 One previous investigation reports that the number of consultations in gastroenterological practices and corresponding diagnoses related to gastroenterological illness decreased gradually during the COVID-19 pandemic. 17 Jördens and colleagues reported a reduction of 19% in the rate of gastro-intestinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…15 This observation could also be a result of a reporting bias in cases where the initial diagnosis of viral pneumonia in association with a suspected COVID-19 infection was established, but not revised promptly after ruling out SARS-CoV-2 by means of polymerase chain reaction testing. 16 One previous investigation reports that the number of consultations in gastroenterological practices and corresponding diagnoses related to gastroenterological illness decreased gradually during the COVID-19 pandemic. 17 Jördens and colleagues reported a reduction of 19% in the rate of gastro-intestinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…An overall of 3651 samples, from 2825 patients and 145 controls, were extracted from the 39 included studies. The studies were conducted worldwide; 16 in Asia [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 14 in Europe [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and 9 in North America [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A minority of studies (8) included control samples [ 21 , 28 , 29 , 33 , 38 , 47 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, digital PCR was able to resolve a few ambiguous RT-qPCR results, detecting the SARS-CoV-2 virus in 17 cases of SARS-CoV-2 reported as equivocal (16/17) or negative (1/17) from 29 close contacts [ 22 ]. Marchio et al also demonstrated the ability of ddPCR to clarify RT-qPCR ambiguous cases, reporting as positive 2/8 equivocal samples [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations